Electronic symptom monitoring in pediatric patients hospitalized for chemotherapy. Issue 16 (4th May 2021) - Leahy, Allison Barz; Schwartz, Lisa A.; Li, Yimei; Reeve, Bryce B.; Bekelman, Justin E.; Aplenc, Richard; Basch, Ethan M.
Abstract : Background: Using patient‐reported outcomes for symptom monitoring in oncology has resulted in significant benefits for adult patients with cancer. The feasibility of this approach has not been established in the routine care of children with cancer. Methods: The Pediatric Patient‐Reported Outcomes version of the Common Terminology Criteria for Adverse Events (Ped‐PRO‐CTCAE) is an item library that enables children and caregivers to self‐report symptoms. Ten symptom items from the Ped‐PRO‐CTCAE were uploaded to an online platform. Patients at least 7 years old and their caregivers were prompted by text/email message to electronically self‐report daily during a planned hospitalization for chemotherapy administration. Symptom reports were emailed to the clinical team caring for the patient, but no instructions were given regarding the use of this information. Rates of patient participation and clinician responses to reports were systematically tracked. Results: The median age of the participating patients (n = 52) was 11 years (range, 7‐18 years). All patients and caregivers completed an initial login, with 92% of dyads completing at least 1 additional symptom assessment during hospitalization (median, 3 assessments; range, 0‐40). Eighty‐one percent of participating dyads submitted symptom reports on at least half of hospital days, and 54% submitted reports on all hospital days. Clinical actions were taken in response to symptom reports 21% of the time. Most patients felt that the system was easy (73%) and important (79%). Most clinicians found symptom reports easy to understand and useful (97%). Conclusions: Symptom monitoring using patient‐reported outcome measures for hospitalized pediatric oncology patients is feasible and generates data valued by clinicians and patients. Abstract : Patient‐ and caregiver‐reported symptom monitoring is feasible for children hospitalized for chemotherapy, and clinicians are willing to use patient‐reported symptom data to make clinical decisions.